Sistem Pengendalian Intern Memoderasi Pengaruh Komitmen Organisasi, Sistem Akuntansi Keuangan Daerah Pada Ketepatanwaktu Pelaporan Keuangan - Eristanti, Baiq Dwi Apryana; Hermanto, Hermanto; Putra, I Nyoman Nugraha Ardana (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
This study aims to determine the effect of organizational commitment and regional financial accounting systems on the timeliness of financial reporting with the internal control system as a moderating variable. The data collection of this study used a questionnaire distributed on 33 OPDs in the West Lombok Regency Government. The research population was accounting staff at 33 OPDs in the West Lombok District Government. The study sample used purposive sampling so that the samples in each Regional Device Organization (OPD) were as many as 3 (three) respondents namely PPK, treasurer of expenditure and accounting staff. The statistical method used to test the hypothesis is the Moderated Regression Analysis (MRA) or interaction test. The results of hypothesis testing are organizational commitment and regional financial accounting systems have a positive effect on the timeliness of financial reporting. The internal control system weakens the influence of organizational commitment on timeliness. Internal control system strengthens the influence of the regional financial accounting system on timeliness. Keywords : Timeliness, Organizational Commitment, Regional Financial Accounting System, Internal Control System